Apocalyptic Representations of Jerusalem. - Maria Leppäkari (Numen Book Series, 2006)
Jerusalem as a symbolic expression of hope attracts attention and religious adherence in relation to its physical presence. The study identifies, traces and examines apocalyptic representations of Jerusalem, and illustrates what happens when these become experienced reality. The empirical part of the book shows how these representations become living images in two contemporary groups' activity in Jerusalem. Private and public endtime representations of Jerusalem provide meaningful models for interpreting the religious past, present and future. The interplay of these representations also shapes our present images of Jerusalem.